Snowflakes fall - MacLachlan, Patricia (New York : Random House, 2013)
In this illustrated poem in honor of the victims of the 2012 shooting in Newtown, Connecticut, falling snowflakes celebrate the uniqueness of life, its precious, simple moments, and the strength of memory.
Keywords: Snow -- Juvenile fiction